Financial Literacy Model for MSMEs as a Financial Performance Measurement Tool (Case Study of MSMEs in Bogor, Depok, and Kuningan) - Sri Setiawati; Hari Gursida; Yohanes Indrayono (Riviera Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy; however, they encounter various challenges in effectively managing their finances. Financial literacy serves as a pivotal factor influencing the financial performance of MSMEs. This study seeks to analyze the correlation between financial literacy and the financial performance of MSMEs across three regions: Bogor, Depok, and Kuningan. A quantitative study methodology was employed, utilizing a survey of MSME owners as respondents. Data were gathered through a questionnaire to assess financial literacy and financial performance, measured by profitability, operational efficiency, and business sustainability indicators. The findings indicate a significant relationship between the financial literacy level and MSMEs' financial performance. MSMEs exhibiting higher levels of financial literacy tend to demonstrate superior financial performance compared to those with lower levels of financial literacy. The implications of this study emphasize the necessity of enhancing financial education programs for MSME stakeholders to improve their capabilities in efficiently managing business finances.